Knowledge-oriented leadership, knowledge management behaviour and innovation performance in project-based SMEs. The moderating role of goal orientations. Issue 8 (13th July 2020) - Zia, Najam Ul
Abstract : Purpose: This study aims to examine the association of knowledge-oriented leadership (KOL), knowledge management (KM) behaviour and innovation performance in project-based small and medium-sized enterprises. It investigates the moderation of goal-orientation in the relationship of KOL with knowledge-acquisition, transfer, documentation and application. Design/methodology/approach: Data are collected from 215 employees in 32 small project-based software firms in Pakistan. Partial least square is used to test the hypotheses. Findings: KOL is positively associated with KM behaviour and innovation performance. KM mediates the relationship of KOL and innovation performance. Furthermore, goal orientations play a moderating role in the relationship of KOL with knowledge acquisition, transfer and application activities. Originality/value: This study extends the literature on knowledge-based dynamic capabilities, by examining the relationship of KOL, KM behaviour and project-based innovation performance. Investigating the moderation of goal-orientation in the relationship of KOL with KM behaviour is also an original contribution.